Understanding the role of power and its relationship to the implementation of the polio eradication initiative in india - Majumdar, Piyusha; Gupta, S. D.; Mangal, D. K.; Sharma, Neeraj; Kalbarczyk, Anna (Frontiers in Health Services, 2022)
Power is exercised everywhere in global health, although its presence may be more apparent in some instances than others. Studying power is thus a core concern of researchers and practitioners working in health policy and systems research (HPSR), an interdisciplinary, problem-driven field focused on understanding and strengthening multilevel systems and policies. This paper aims to conduct a Power analysis manifested by the actors involved in Polio Program Implementation. It will also reflect how different power categories exerted by actors and embedded in strategies to combat program implementation challenges while planning and executing Global Polio Eradication Initiative. We have collected quantitative and qualitative data of stakeholders who were part of Polio Universe as a part of Synthesis and Translation of Research and Innovations from the Polio Eradication Project. Key informants were main actors of the polio eradication program, both at the national and sub-national levels. Research tools designed to explore the challenges, strategies, unintended consequences in implementing the polio eradication program in India. Understanding Power has gradually come to be recognized as an essential parameter to understand global governance and health. Stakeholders involved during polio program implementation have exerted different kind of power from structural to discursive, moral power wielded by religious leaders to institutional Power, expert Power used by professional doctors to commoners like female vaccinators, and network power exercised by community influencers. Hidden power was also demonstrated by powerless actors like children bringing mothers to polio booths. Power is not a finite resource, but it can be used, shared, or created by stakeholders and networks in multiple ways. Those people who seem to be powerless possess invisible power that can control an individual's decision. Moreover, these power categories are not mutually exclusive and may be deeply interconnected with each other; one type of power can be transformed into another. Power and relations play an important role in influencing the decision-making of the community and individuals. Mid-range theories of core implementation science like PARIHAS and CFIR can also add an important variable of power in their construct necessary for implementation success of any health program.